2018
DOI: 10.1021/jacs.8b06150
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Ordering Coupled to Reconstruction of Basic Building Units during Synthesis of High-Ni Layered Oxides

Abstract: Metal (M) oxides are one of the most interesting and widely used solids, and many of their properties can be directly correlated to the local structural ordering within basic building units (BBUs). One particular example is the high-Ni transition metal layered oxides, potential cathode materials for Li-ion batteries whose electrochemical activity is largely determined by the cationic ordering in octahedra (e.g., the BBUs in such systems). Yet to be firmly established is how the BBUs are inherited from precurso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
107
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 126 publications
(120 citation statements)
references
References 69 publications
4
107
0
Order By: Relevance
“…A strong temperature dependence of the kinetics of cationic ordering is observed as a result of thermal‐driven oxidation of TM ions and lithium/oxygen loss concomitantly occurring during the heat treatment . After that, they find out that the reaction pathway and the associated Li/Ni mixing/ordering processes of the LiNi 0.77 Mn 0.13 Co 0.1 O 2 depend fundamentally on the symmetry breaking and reconstruction in the NiO 6 octahedra ( Figure a) . In specific, the mobility of Ni 2+ ions highly increases, and thus inclines to mix with Li ions due to the oxygen loss and occurrence of corresponding symmetry breaking in the NiO 6 .…”
Section: Strategies To Mitigate the Surface/interface Structure Degramentioning
confidence: 99%
See 2 more Smart Citations
“…A strong temperature dependence of the kinetics of cationic ordering is observed as a result of thermal‐driven oxidation of TM ions and lithium/oxygen loss concomitantly occurring during the heat treatment . After that, they find out that the reaction pathway and the associated Li/Ni mixing/ordering processes of the LiNi 0.77 Mn 0.13 Co 0.1 O 2 depend fundamentally on the symmetry breaking and reconstruction in the NiO 6 octahedra ( Figure a) . In specific, the mobility of Ni 2+ ions highly increases, and thus inclines to mix with Li ions due to the oxygen loss and occurrence of corresponding symmetry breaking in the NiO 6 .…”
Section: Strategies To Mitigate the Surface/interface Structure Degramentioning
confidence: 99%
“…As discussed above, the content of Li residues and the level of cation disorder depend highly on the synthetic conditions, particularly for the contributions from the particle size, Li‐excess content, calcination temperature, calcination atmosphere, and heating/cooling rate. In particular, Wang et al investigate the kinetic and thermodynamic aspects of cationic ordering during synthesis of Ni‐rich cathodes by adjusting the sintering temperature and time . Among these investigations, the kinetic reaction pathway and cationic ordering in the intermediates toward forming NCM701515 when subjected to heat treatment at three different temperatures (800, 850 and 900 °C) are tracked by in situ time‐resolved techniques .…”
Section: Strategies To Mitigate the Surface/interface Structure Degramentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is critical to develop in situ techniques to probe the structural evolution during the formation of Ni-rich cathodes. [70] Li et al have used synchrotron in situ XRD to monitor the solid-state synthesis process of NCM622 cathodes. [71] Their results found that both preheating step and the calcination temperature play a critical role in controlling the phase composition of Ni-rich cathodes and minimizing the content of Li 2 CO 3 and NiO impurity, both of which are detrimental to the specific capacity and cycle stability of the final Ni-rich cathodes.…”
Section: Synthetic Controlmentioning
confidence: 99%
“…To overcome the above problems, a great number of strategies have been explored to boost the physical and chemical stability of this cathode by morphology design, surface modi-cation and interior ionic doping. [17][18][19][20][21][22][23][24][25] Various of coating substances including metal oxides, metal phosphates and metal uorides have been used to stabilize the interface between electrode and electrolyte. Although the coating layer could stabilize the structure of the interface region and alleviate the side reaction between electrode and electrolyte, the approach for construction of modication layer usually need post coating process, thus increasing the complexity of material manufacture.…”
Section: Introductionmentioning
confidence: 99%